Caribbean curatorial agencies: A Cultural Object’s unruliness and its affective aftermaths - Garrido Castellano, Carlos (2016)
This essay analyzes A Cultural Object, an installation made by the Jamaican artist Dawn Scott in 1985, in order to discuss how institutional practices and criticism are framed in contemporary Caribbean art. Through an examination of A Cultural Object’s afterlife in the space of the National Gallery of Jamaica, I attempt to examine the relation between the agencies of the museum, the artist, the spectators, and the installation. In so doing, the text intends to reconsider the potential of unpredictable human and nonhuman relations within Caribbean institutional and cultural spaces.